Legal development of the investment dispute settlement system in Vietnam: Issues on the investor-state dispute settlement - Maomi, Iwase (H. : ĐHQGHN, 2017)
This article analyzes development of legal systems on ISDS in Vietnam, focusing on both the IIAs concluded by Vietnam with the Netherlands, France and the U.S. respectively, and Vietnam’s municipal laws dealing with foreign investment dispute settlement, such as laws on investment, BOT and commercial arbitration. Through this analysis, the author examines issues on settlement of disputes between foreign investors and the Vietnamese government and/or SOEs